Individual factor structure of qualified volleyball players' preparedness - Zh.L. Kozina; S.B. Khrapov; S. Yevstratov; N.A. Kolomiets; S.V. Hryshchenko; A.O. Minenok; Iu.M. Nosko (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
The purpose of the study was to develop individual factor models of physical preparedness of high-level volleyball players of different game roles. Matherial and methods. The study was attended by 12 players of the Kharkiv woman women team in Kharkiv Volleyball players were tested for 10 indicators of pedagogical pedagogical testing: Running to 4 points; Running for determining the speed of movement along the volleyball court at a distance of 30 m (9-3-6-3-9 m); Jump in height from place; Jump in height from run; Throwing a stuffed ball from the starting position sitting; Throwing a stuffed ball from the starting position is lying; Lifting of the body from the position lying on the back for 20 s (number of times); Elevation of body from the position of lying on the stomach for 20 s (number of times); The flexion-extension of the hands in the emphasis lying for 20 s (number of times); Leap length from space. The obtained data were mathematically processed using factor analysis methods, on the basis of which the individual factor models of players were constructed. Results. On the basis of factor analysis, the structure of qualified volleyball players' preparedness was determined, in which four expressed factors were expressed: speed-strength training, relative strength, special endurance, high endurance. The model of the belonging of the players to the role is determined according to the determined factor structure: in the attackers of the first pace, the following factors are factors such as speed-power preparedness and relative strength, at attackers of the second pace - speed-power preparedness and fast endurance, fast endurance and special endurance, in Libero - relative strength and special endurance. Conclusion. Using the developed scheme, the individual factor models of players and the developed scale of assessments of the test indicators, one can determine the individual potential opportunities of different players to the game in different roles.